2012
DOI: 10.1016/j.solmat.2012.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Electronic properties of grain boundaries in Cu(In,Ga)Se2 thin films with various Ga-contents

Abstract: We present a study on the electronic properties of grain boundaries (GBs) in polycrystalline Cu(In,Ga)Se 2 (CIGSe) thin films. As grown as well as KCN-treated films were comparatively investigated. No influence of the chemical treatment on the electronic properties of GBs was found. GBs in general exhibited a large variation of their electronic properties. By means of a novel method of data analysis, both potential barriers for holes and electrons were found at GBs, in a range from-118mV to +114mV, as well as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 29 publications
2
19
0
Order By: Relevance
“…Baier et al . reported that the work function of an as‐grown (1 h exposed to air) CIGS sample was ~4.4 eV, and that of a chemically etched CIGS sample was ~4.8 eV . Our work function value for the CIGSSe samples averaged ~4.72 eV with deionized water etching, and this corresponds to the values presented by the other groups.…”
Section: Resultssupporting
confidence: 77%
See 3 more Smart Citations
“…Baier et al . reported that the work function of an as‐grown (1 h exposed to air) CIGS sample was ~4.4 eV, and that of a chemically etched CIGS sample was ~4.8 eV . Our work function value for the CIGSSe samples averaged ~4.72 eV with deionized water etching, and this corresponds to the values presented by the other groups.…”
Section: Resultssupporting
confidence: 77%
“…We should mention that Ga and S influenced the work function of the CIGSSe thin films. In a previous study, the work function of GBs in CIGSe absorber layer did not depend on Ga content . However, a correlation between the work function and S/(S + Se) composition ratio of Cu 2 ZnSn(S,Se) 4 (CZTSSe) was observed in KPFM measurements .…”
Section: Resultsmentioning
confidence: 75%
See 2 more Smart Citations
“…In Cu , it can be seen that the electronic structures at GBs are significantly influenced by the defects. A recent experimental study [26] on electronic properties of GBs in polycrystalline Cu(In,Ga)Se 2 thin films may confirm the results. The thin films were studied by a Kelvin probe force microscopy in an ultrahigh vacuum (UHV) environment.…”
Section: Discussionsupporting
confidence: 66%